2013
DOI: 10.1186/1471-2458-13-568
|View full text |Cite
|
Sign up to set email alerts
|

Challenges to evaluating complex interventions: a content analysis of published papers

Abstract: BackgroundThere is continuing interest among practitioners, policymakers and researchers in the evaluation of complex interventions stemming from the need to further develop the evidence base on the effectiveness of healthcare and public health interventions, and an awareness that evaluation becomes more challenging if interventions are complex.We undertook an analysis of published journal articles in order to identify aspects of complexity described by writers, the fields in which complex interventions are be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
181
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(191 citation statements)
references
References 53 publications
(68 reference statements)
2
181
0
8
Order By: Relevance
“…The Canadian Institutes of Health Research demonstrated their interest by funding the International Collaboration on Complex Interventions (involving investigators from Canada, the United States, the United Kingdom, and Australia), which produced some of the key papers in these debates (7,16,31,34,36,55,62,65,67,94,96,98,110,120,128,129). This collaboration also enabled a partnership with the Centers for Disease Control and Prevention and the Prevention Research Centers with conferences in Chicago in 2009 (128), Montréal in 2010 (27), and Toronto in 2011 to advance theories and methods.…”
Section: The Complex Interventionmentioning
confidence: 99%
“…The Canadian Institutes of Health Research demonstrated their interest by funding the International Collaboration on Complex Interventions (involving investigators from Canada, the United States, the United Kingdom, and Australia), which produced some of the key papers in these debates (7,16,31,34,36,55,62,65,67,94,96,98,110,120,128,129). This collaboration also enabled a partnership with the Centers for Disease Control and Prevention and the Prevention Research Centers with conferences in Chicago in 2009 (128), Montréal in 2010 (27), and Toronto in 2011 to advance theories and methods.…”
Section: The Complex Interventionmentioning
confidence: 99%
“…By definition, such actions can be broadly conceived of as social interventions, as they are, in effect, purposeful attempts to change social contexts (as well as economic and environmental factors) that may in part influence patterns of lifestyle, behaviours and health outcomes (Poland et al, 2008). Despite its importance, a more nuanced interpretation of context is still not routinely integrated into the evaluation of initiatives in the public health field (Datta & Petticrew, 2013). This is particularly the case in relation to social aspects of context (Shoveller et al, 2015) despite the recognition that social relations lie 'at the heart of any social intervention' (Poland et al, 2008, p. 301).…”
Section: Introductionmentioning
confidence: 99%
“…As public health researchers and practitioners increasingly embrace (rather than ignore) complexity perspectives, several distinct methodological challenges arise when conducting meta-analyses of intervention effects (26). In addition to questions about whether and to what magnitude an intervention yielded intended effects, consideration of complexity warrants questions regarding for whom and in which contexts interventions are more (or less) effective, which intervention components are most (or least) essential, and how and why the intervention yielded effects (or not).…”
Section: Meta-analytic Techniques For Estimating Effects Of Complex Pmentioning
confidence: 99%